EXPERT EVALUATION OF FORMATION AND DEVELOPMENT OF COMPETENCE IN LABOUR AND CIVIL PROTECTION STUDIES - Brizga, Dace; Ruba, Jelena; Miezite, Olga; Sisenis, Linards (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Labour protection specialists need to improve and develop their competence in order to ensure a safe, healthy and sustainable working environment in the relevant economic sector. Competence and its components, as well as the criteria and parameters are very important factors in the formation and development of competence in adult education. The aim of the study was to carry out expert evaluation of the developed competence components’ model in labour and civil protection as well as the criteria and parameters, basing on the analysis of theoretical knowledge. The methodological basis included studies, analyses and evaluation of the relevant publications in the context of the competence - components of competence their criteria and carrying out an expert evaluation of the component model, its parameters and criteria. The expert evaluation found that it is necessary to replace the communication component in the model of competence components with the component of intelligibility. The evaluation of intuition, skills, attitude and professional ethics are those were in most cases consensus was reached, thus being unanimously evaluated. Unanimous were also the evaluations of knowledge, creativity, emotional intelligence and reflection. A relatively low level of consensus was reached in the evaluation of communication. Attitude as a component of competence was unanimously ranked first in terms of significance.